Leading in a Complex Healthcare Ecosystem - Pittman, Janice; Kolakowski, Matthew (Journal of Leadership, Accountability and Ethics, 2020)
Today's healthcare environment requires an examination of what it means to be a fully competent leader. As a result, an upsurge in interest in healthcare management competencies has resulted. The present study utilizes a diverse group of informants as health management practitioners, multi-disciplinary faculty groups, and health service consumers. Using the competency directory published by the Healthcare Leadership Alliance (HLA), this study examined which traits are essential in providing quality healthcare services. Using survey data collected from 139 respondents, this study reveals that leadership was the only statistically significant competency